S07: Health Promotion in the Physical Education Setting (Baltic Journal of Sport and Health Sciences, 2026)
This symposium explores the promotion of health-enhancing physical activity (HEPA) through innovative practice and research initiatives situated in physical education (PE) contexts across different European countries. With a shared aim of advancing physical literacy (PL), upskilling PE teachers, and enhancing student engagement, the symposium features one EU-funded policy/practice project and three research-oriented studies addressing diverse educational stages and methodological approaches:·         The first presentation introduces ePhyLi, an Erasmus+ Sport funded project designed to enhance university students’ knowledge and understanding of PL, equipping future PE teachers to become advocates of meaningful, healthy, active lifestyles. Implemented across the EU and supported by EUPEA, the project has developed multilingual digital tools, including an e-book, a mobile application, and a gamified e-learning platform, currently undergoing pilot testing to assess educational impact, usability, and user experience.·         The second presentation reports on a Romanian study evaluating the effectiveness of Kahoot! platform for enhancing PE lessons aimed at improving fifth-grade students’ theoretical knowledge and understanding of PL. Employing an experimental design, the study revealed significant learning gains in the experimental group, reinforcing the potential of digital gamification elements to enhance engagement and learning in PE and Health classes.·         Our third presentation reports on the PLACE intervention, an extracurricular programme in Germany designed to promote children’s HEPA through a PL framework. Using a mixed-methods design, the study compared the intervention with regular PE across five dimensions of quality experiences. Findings revealed that PLACE was particularly effective in enhancing children’s cognitive activation and affective engagement in sport, underscoring the importance of co-design and respect for individuality in fostering PL-based, child-centred active lifestyles.·         Finally, a study from Latvia examines the relationship between students’ physical fitness levels and their engagement in PE and Health classes across age groups. Drawing on data from fitness assessments, surveys, and pedagogical observations, the findings demonstrate that students with higher physical fitness levels exhibit increased engagement, highlighting the need for more inclusive and differentiated pedagogical approaches for developing PL.Together, the four contributions underscore the importance of effective high-quality pre- and in-service training, innovative pedagogies, and inclusive practices in nurturing engagement in lifelong HEPA. The symposium demonstrates how digital innovation, collective approaches, and differentiated instruction can empower educators and learners collectively, contributing to developing PL and broader public health goals in and through PE.Keywords: Physical education, physical literacy, digital tools, health; professional development